2009
DOI: 10.1016/j.ejcts.2009.01.005
|View full text |Cite
|
Sign up to set email alerts
|

In vitro results of a new minimally invasive aortic valve resecting tool☆☆☆

Abstract: Background: Aortic valve replacement (AVR) using extracorporeal circulation is currently the treatment of choice for symptomatic aortic stenosis. However, patients with multiple high-risk comorbid conditions may benefit from reduced ECC time by a simplified and faster resection in conjunction with quick sutureless valve implantation. Methods: A prototype of a new minimally invasive aortic valve resection tool equipped with rotating and foldable Nitinol cutting edges was designed. Commercially available aortic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 21 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…The concept of pretreating the native valve has been discussed and proposed including valve debulking, modification and removal (9,(13)(14)(15). Substantial acute aortic insufficiency can occur during aortic valve pretreatment, and the hemodynamic protection of the TAV can allow for the development of valve pretreatment from concept to reality.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of pretreating the native valve has been discussed and proposed including valve debulking, modification and removal (9,(13)(14)(15). Substantial acute aortic insufficiency can occur during aortic valve pretreatment, and the hemodynamic protection of the TAV can allow for the development of valve pretreatment from concept to reality.…”
Section: Discussionmentioning
confidence: 99%
“…Aortic valve resection was first introduced by our group in 2005 using a water-jet scalpel and a resection chamber using a Hol:YAG laser. 17 In 2009, Wendt et al 18 reported on a minimally invasive aortic valve resection tool equipped with rotating and foldable Nitinol (Nitinol Devices & Components, Inc., Fremont, CA USA) cutting edges. Other aortic valve resection devices were presented by Bombien et al 19 in 2010 using a valve isolation chamber and by Astarci et al 20 in 2011 using a circular blade.…”
Section: Discussionmentioning
confidence: 99%
“…The diameter of the device is still large, but this can be reduced in the next prototypes. The goal of this device is the controlled resection by grip and not by oscillating blades, 13 which will reduce the risk for any injury to the aortic root. Furthermore, the direct implantation option with the crimped valve, ''parked'' in the ascending aorta, offers an effective valve deployment.…”
Section: Discussionmentioning
confidence: 99%